Cobweb theorems with production lags and price forecasting - Daniel Dufresne; Felisa Vázquez-Abad (Kiel Institute for the World Economy (IfW), 2012)
The classical cobweb theorem is extended to include production lags and price forecasts. Price forecasting based on a longer period has a stabilizing effect on prices. Longer production lags do not necessarily lead to unstable prices; very long lags lead to cycles of constant amplitude. The classical cobweb requires elasticity of demand to be greater than that of supply; this is not necessarily the case in a more general setting, price forecasting has a stabilizing effect. Random shocks are also considered.
Keywords: C02; C62; C65; D58; E32; 330; Cobweb theorem; production lags; stable markets; price fluctuations; Cobweb; Preis; Prognose; Gleichgewichtsstabilität; Produktion; Lag-Modell; Theorie